2016
DOI: 10.3389/fimmu.2016.00111
|View full text |Cite
|
Sign up to set email alerts
|

A New, Potent, and Placenta-Permeable Macrolide Antibiotic, Solithromycin, for the Prevention and Treatment of Bacterial Infections in Pregnancy

Abstract: Intrauterine infection–inflammation is a major cause of early preterm birth and subsequent neonatal mortality and acute or long-term morbidity. Antibiotics can be administered in pregnancy to prevent preterm birth either prophylactically to women at high risk for preterm delivery, or to women with diagnosed intrauterine infection, prelabor rupture of membranes, or in suspected preterm labor. The therapeutic goals of each of these scenarios are different, with different pharmacological considerations, although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 118 publications
1
16
0
Order By: Relevance
“…(Urushiyama et al, 2017;Kayem et al, 2018;Zhu et al, 2018). Interestingly, bacterial species typically associated with ascending intrauterine infection and preterm labor were not detected in this study (Keelan et al, 2016). This supports the view that invasion by such species represents a pathological event that likely occurs after 20 weeks' gestation, whereas potential colonization by the species identified in this study occurs much earlier and is non-pathogenic.…”
Section: Description Of Bacterial Dna Profiles In Mid-trimester Amniosupporting
confidence: 83%
“…(Urushiyama et al, 2017;Kayem et al, 2018;Zhu et al, 2018). Interestingly, bacterial species typically associated with ascending intrauterine infection and preterm labor were not detected in this study (Keelan et al, 2016). This supports the view that invasion by such species represents a pathological event that likely occurs after 20 weeks' gestation, whereas potential colonization by the species identified in this study occurs much earlier and is non-pathogenic.…”
Section: Description Of Bacterial Dna Profiles In Mid-trimester Amniosupporting
confidence: 83%
“…Compared with other existing macrolides, it has a higher rate of transplacental passage . Animal studies have shown that the risk of developmental toxicity and/or teratogenesis was low with no mutagenic or clastogenic effects and with low hepatotoxicity …”
Section: Therapeutic Options For Genital Ureaplasma Infection In Pregmentioning
confidence: 99%
“…Many of the trials of prophylactic antibiotic therapy given to pregnant women to prevent PTB have failed to employ robust inclusion criteria or delivered poorly effective antibiotic regimens (95, 96). Identifying women who will benefit from treatment is a key requirement for primary prevention: prescribing antibiotics to large numbers of women in pregnancy in order to prevent PTB in a small percentage of recipients is not justifiable in light of the emerging recognition of the potential developmental effects of disrupting the maternal and neonatal microbiomes with antibiotics in pregnancy (97100). …”
Section: Prevention Of Infection-driven Ptbmentioning
confidence: 99%
“…It remains to be determined whether more refined and selective molecular techniques may help to improve diagnostic discrimination (109). It is likely that a combination of clinical risk factors (e.g., prior PTB, cervical imaging, and abnormality detection), high-resolution microbial profiling (possibly including bacterial strain identification), and immunological/inflammatory biomarker assessment will be needed, in combination with a highly effective antimicrobial regimen (97, 126), to enable a truly effective maternal “screen and treat” program to achieve the desired level of precision and effectiveness required for a primary prevention public health program (127133). …”
Section: Prevention Of Infection-driven Ptbmentioning
confidence: 99%